Effectiveness of the BNT162b2 mRNA Covid-19 vaccine in Spanish healthcare workers - Núñez López, Concepción (Enferm Infecc Microbiol Clin, 2023)
INTRODUCTION: Frontline health care workers (HCW) have higher risk than the general population to become infected by SARS.CoV.2, so they were a priority group for Covid-19 vaccine administration. We compared the incidence and prevalence of HCW infected pre-and post-vaccination with the BNT162b2 mRNA COVID-19 vaccine. MATERIAL AND METHODS: Prospective observational study carried out between 01/12/20 and 07/03/21 in La Paz University Hospital, Madrid (Spain). SARS.CoV.2 positive cases in HCW after vaccination were collected and compared to those hospitalized COVID-19 patients at the same hospital. RESULTS: Two weeks after finishing the first round of vaccinations daily new cases of HCW infections (symptomatic and asymptomatic) decreased substantially and cumulative cases of infected HCW and hospitalized COVID-19 patients started to diverge. No new positive cases of HCW infection were registered seven days after the second dose of BNT162b2 mRNA COVID-19 vaccine. CONCLUSIONS: BNT162b2 mRNA COVID-19 vaccine is highly effective in Spanish HCW.